Exemplifying the Effects Using WetSpass Model Depicting the Landscape Modifications on Long-Term Surface and Subsurface Hydrological Water Balance in Bilate Basin, Ethiopia - Abera Shigute Nannawo; Tarun Kumar Lohani; Abunu Atlabachew Eshete (Advances in Civil Engineering)
The alteration of spatial patterns of landscape interrupts water balance components in Bilate basin of Ethiopia. The aim is to characterize the spatio-temporal variation of surface-subsurface hydrological water balance using the WetSpass model comprising of soil type, topography, groundwater depth, and slope. Environment for Visualizing Images (ENVI) and Arc-GIS software were assimilated for the classification of Landsat images from 1989 to 2019 replicating the forest, shrub, and grasslands which decrease by 4.0%, 9.41%, and 14.87%, respectively, and agricultural land increasing by 27.06% from 1989 to 2019. The goodness of fit in surface runoff and subsurface flow for the two model outputs with the square of regression (R2) of 0.79 and 0.81, while the root mean square errors (RMSEs) 8.26 mm and 8.39 mm for 1989 and 2019, respectively, were calculated. Average annual interception, groundwater recharge, surface runoff, and actual-evapotranspiration were 36.4 mm, 127.34 mm, 614.95 mm, and 517.59 mm, respectively, revealing that WetSpass works remarkably in simulating the components of the hydrological water balance.